Deleterious Effects of Remote Ischaemic Per-conditioning During Lower Limb Ischaemia–Reperfusion in Mice. (December 2021) - Guillot, Max; Charles, Anne-Laure; Lejay, Anne; Pottecher, Julien; Meyer, Alain; Georg, Isabelle; Goupilleau, Fabienne; Diemunsch, Pierre; Geny, Bernard
Abstract : Objective: The aim of this study was to investigate whether remote ischaemic per-conditioning might protect skeletal muscle during lower limb ischaemia–reperfusion (IR). Methods: Twenty-three male C57BL/6 mice were randomised into three groups: sham group ( n = 7), IR group (unilateral tourniquet induced three hours of ischaemia followed by 24 hours of reperfusion, n = 8), and remote ischaemic per-conditioning group (RIPerC) (three cycles of 10 minute IR episodes on the non-ischaemic contralateral hindlimb, n = 8). Oxygraphy, spectrofluorometry, and electron paramagnetic resonance spectroscopy were performed in order to determine mitochondrial respiratory chain complexes activities, mitochondrial calcium retention capacity (CRC) and reactive oxygen species (ROS) production in skeletal muscle. Results: IR impaired mitochondrial respiration (3.66 ± 0.98 vs. 7.31 ± 0. 54 μmol/min/g in ischaemic and sham muscles, p = .009 and p = .003 respectively) and tended to impair CRC (2.53 ± 0.32 vs. 3.64 ± 0.66 μmol/mg in ischaemic and sham muscles respectively, p = .066). IR did not modify ROS production (0.082 ± 0.004 vs. 0.070 ± 0.004 μmol/min/mg in ischaemic and sham muscles respectively, p = .74). RIPerC failed to restore mitochondrial respiration (3.82 ± 0.40 vs. 3.66 ± 0.98 μmol/min/g in ischaemic muscles from the RIPerC group and the IR group respectively, p = .45) and CRC (2.76 ± 0.3 vs. 2.53 ± 0.32 μmol/mg in ischaemic muscles from the RIPerC group and the IR group respectively, p = .25). RIPerC even impaired contralateral limb mitochondrial respiration (3.85 ± 0.34 vs. 7.31 ± 0. 54 μmol/min/g in contralateral muscles and sham muscles respectively, –47.3%, p = .009). Conclusion: RIPerC failed to protect ischaemic muscles and induced deleterious effects on the contralateral non-ischaemic muscles. These data do not support the concept of RIPerC.